Chemically different non-thermal plasmas target distinct cell death pathways - Lunov, Oleg; Zablotskii, Vitalii; Churpita, Olexander; Lunova, Mariia; Jirsa, Milan; Dejneka, Alexandr; Kubinová, Šárka (Scientific reports, 2017)
A rigorous biochemical analysis of interactions between non-thermal plasmas (NTPs) and living cells has become an important research topic, due to recent developments in biomedical applications of non-thermal plasmas. Here, we decouple distinct cell death pathways targeted by chemically different NTPs. We show that helium NTP cells treatment, results in necrosome formation and necroptosis execution, whereas air NTP leads to mTOR activation and autophagy inhibition, that induces mTOR-related necrosis. On the contrary, ozone (abundant component of air NTP) treatment alone, exhibited the highest levels of reactive oxygen species production leading to CypD-related necrosis via the mitochondrial permeability transition. Our findings offer a novel insight into plasma-induced cellular responses, and reveal distinct cell death pathways triggered by NTPs.
Keywords: Animals; DNA Damage; apoptóza; buněčné linie; oxidační stres; Apoptosis; Oxidative Stress; Mice; nekróza; Spectroscopy, Fourier Transform Infrared; Reactive Oxygen Species; signální transdukce; reaktivní formy dusíku; myši; Signal Transduction; buněčná smrt; buňky NIH 3T3; Cell Line; NIH 3T3 Cells; Necrosis; spektroskopie infračervená s Fourierovou transformací; poškození DNA; Cell Death; reaktivní formy kyslíku; Reactive Nitrogen Species; helium; zvířata; plazmové plyny; Helium; Plasma Gases